Manajemen Ekonomi Islam dalam Menangani Pandemi Coronavirus Disease (COVID-19) di Indonesia - Sumarni, Yenti (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2020)
This COVID-19 case can affect macroeconomic aspects in general. In this journal, aspects of previously published by McKibbin and Wilcoxen will be developed of Warwick McKibbin and Roshen Fernando. In this Journal will analyze sharia management on transactions using money by the Central Bank, nominal wages and financial policy. The journal uses qualitative research methods with natural research methods because the research is conducted in natural conditions. The findings of this study are First, transactions using the central bank. The concept of Islamic economics, transactions using official money issued by the government. money is used in transactions for activities that work and works as a precaution in an emergency conversation. Second, the nominal payment has been realized properly in accordance with the Islamic economy, it can be seen from the policies set by the government and related ministries. The third concerning economic policy has objectives related to Islamic economics. For further research, it is expected to conduct research on asset accounts and fund flows and the merging of two different models between households and companies so that aspects of McKibbin and Wilcoxen can be full analyzed.